Proximal renal tubular acidosis with and without Fanconi syndrome - Ibrahim Kashoor; Daniel Batlle (The Korean Society of Nephrology, 2019)
Proximal renal tubular acidosis (RTA) is caused by a defect in bicarbonate (HCO3−) reabsorption in the kidney proximal convoluted tubule. It usually manifests as normal anion-gap metabolic acidosis due to HCO3− wastage. In a normal kidney, the thick ascending limb of Henle's loop and more distal nephron segments reclaim all of the HCO3− not absorbed by the proximal tubule. Bicarbonate wastage seen in type II RTA indicates that the proximal tubular defect is severe enough to overwhelm the capacity for HCO3− reabsorption beyond the proximal tubule. Proximal RTA can occur as an isolated syndrome or with other impairments in proximal tubular functions under the spectrum of Fanconi syndrome. Fanconi syndrome, which is characterized by a defect in proximal tubular reabsorption of glucose, amino acids, uric acid, phosphate, and HCO3−, can occur due to inherited or acquired causes. Primary inherited Fanconi syndrome is caused by a mutation in the sodium-phosphate cotransporter (NaPi-II) in the proximal tubule. Recent studies have identified new causes of Fanconi syndrome due to mutations in the EHHADH and the HNF4A genes. Fanconi syndrome can also be one of many manifestations of various inherited systemic diseases, such as cystinosis. Many of the acquired causes of Fanconi syndrome with or without proximal RTA are drug-induced, with the list of causative agents increasing as newer drugs are introduced for clinical use, mainly in the oncology field.